CUPRESSUS DUPREZIANA: A DENDROCLIMATIC RECORD FOR THE MIDDLE-LATE HOLOCENE IN THE CENTRAL SAHARA - Cremaschi M.; Pelfini M.; Santilli M. (My University, 2006)
Dendroclimatology of Cupressus dupreziana, the Tassili cypress, has been attempted on samples obtained from the door beams of the old cities of Ghat and Barkat located at the foot of the Tassili, where the cypress still lives. The tree rings of 20 samples were measured and dated by 24 AMS 14C dates. A mean ring-width chronology has thus been obtained, spanning, though discontinuously, 5220 to 100 14C BP (5990-65 cal. BP). As the tree-ring width in dry lands depends mainly on water availability, the mean ring-width chronology represents a detailed record of changes in rainfall on a decade scale for the middle and late Holocene of the central Sahara. It indicates main drought spells at 5200-5000 14C BP (5900-5760 cal. BP) and at 4350 BP (5120 cal. BP), followed by phases of enhanced precipitation and by the onset of extreme arid conditions at 1550 14C BP (1500 cal. BP).
Keywords: CLIMATIC CHANGE; DENDROCLIMATOLOGY; DROUGHT; TASSILI CYPRESS; CUPRESSUS DUPREZIANA; CENTRAL SAHARA; DESERT ONSET; HOLOCENE; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен